Prenatal Exercise Using Gym Ball for Mrs. N in the Third Trimester of Pregnancy to Reduce Lower Back Pain at Independent Midwife Practice Anisa Mauliddina - Nanik Rahayu; Reni Tri Lestari; Tri Ariani; Eny Retna Ambarwati (International Journal Of Health Science, 2025)
Pregnancy is a physiological condition in which a fetus develops in a woman's uterus. In the third trimester, pregnant women often experience discomfort such as lower back pain due to the enlarged uterus, which causes changes in posture, particularly an enlarged spine (hyperlordosis). Mrs. N is one of the pregnant women who came to PMB Anisa Mauliddina Sleman with complaints of lower back pain in her third trimester. In this case, midwives play a crucial role in helping alleviate discomfort in pregnant women, one of which is through interventions such as prenatal exercises using a gym ball. Objective: To be able to provide prenatal exercise care with a gym ball to Mrs. N during midwifery care during pregnancy at Independent Midwife Practice Anisa Mauliddina. Methode:The type of research method used is descriptive analytic method with a case study approach. This research instrument used the results of examinations, observations or observations of the author, interviews with clients and supporting data listed in the maternal and child health book owned by the client.  The results of research on pain on Ny. N after doing senam gymball 10-15 minutes once every 3 days for 3 days it decreased, starting from the first day pain scale 6 to 2 on day 6. There was a decrease in pain intensity after doing pregnancy exercises with a gym ball on Mrs. N, who was pregnant in the third trimester at Independent Midwife Practice Anisa Mauliddina Godean Sleman.